Knockdown of Circular RNA hsa_circ_PVT1 Inhibited Laryngeal Cancer Progression via Preventing wnt4/β-Catenin Signaling Pathway Activation - Yu, Feng; Lin, Ying; Ai, Mao-Mao; Tan, Guo-Jie; Huang, Jia-Li; Zou, Zi-Rou (Frontiers in Cell and Developmental Biology, 2021)
Aim To explore the function and mechanism of circular has_circ_PVT1 on laryngeal cancer (LC). Methods Microarray chip was performed to screen the differential expression of circRNA. Western blot and qRT-PCR was employed to detect the protein and mRNA level. CCK-8, clone formation, cell cycle, wound healing, and Transwell assay were performed to detect the cell proliferation, migration, and invasion ability. Luciferase assay and Fish were used to confirm the relationship between circ_PVT1/CBX4 and miR-21-5p. Flow cytometry and TUNEL assay were carried out to assess the apoptosis level. Results The upregulation of circ_PVT1 was found in LC tissues and cells. Silencing of circ_PVT1 inhibited LC progression via targeting miR-21-5p and indirectly controlling CBX4. Wnt4/β-catenin signal pathway was inactivated by inhibiting the expression of circ_PVT1. Conclusion Knockdown of circ_PVT1 prevented LC progression via targeting miR-21-5p/CBX4 by inhibiting wnt4/β-catenin signal pathway, which could provide a novel therapeutic target for LC.